Multidimensional Characterization of Mass Transfer during Osmotic Dehydration: Changes in the Properties of Mixed Sugar Solutions and Dehydrated Kiwifruit Chunks - LI Shujuan, WANG Fengzhao, BI Jinfeng, LÜ Jian (Shipin Kexue, 2025)
In this study, using mixed solutions of sucrose (SUC) and fructo-oligosaccharides (FOS), isomalto-oligosaccharides (IMO), or xylo-oligosaccharides (XOS) as the medium, pulsed ultrasound (US)-assisted osmotic dehydration (OD) of kiwifruit chunks was carried out. Changes in the properties of mixed sugar solutions were systematically analyzed during the dehydration process, the quality formation of kiwifruit chunks was examined, and the process of mass transfer during OD was evaluated from a multidimensional perspective. Results showed that US accelerated the mass transfer. Specifically, the content of total soluble solids (TSS), osmotic pressure and conductivity of the mixed sugar solutions significantly decreased and the turbidity increased. US-SUC-XOS group showed the highest TSS content (23.65 °Brix), osmotic pressure (1 439.00 mOsm/L), conductivity (13 316.87 μS/cm) and turbidity (12.50 NTU). During the OD process, the TSS content and osmotic pressure of the mixed sugar solutions decreased, the turbidity increased, and the conductivity decreased first and then increased, indicating that mass transfer took place. Analysis of the quality changes of kiwifruit chunks demonstrated that the TSS content continued to increase. The highest TSS content (15.35 °Brix) was observed in the 12 h US-SUC-XOS group. Additionally, the infiltration of sugars could support cells, resulting in obvious plasmolysis, which in turn contributed to decreased texture properties. Analysis of electrical characteristics demonstrated that US-assisted OD facilitated the movement of charged particles, which was reflected in a decrease in the impedance and reactance values of kiwifruit chunks. Notably, in the US-SUC-XOS group, the adhesion effect slowed down the particle movement, leading to the highest impedance and reactance values. X-ray spectroscopy analysis confirmed the mass transfer of elements. The highest proportion of K (67.08%) and the lowest proportion of Ca (28.61%) were obtained in the 12 h US-SUC-XOS group. Additionally, 1H nuclear magnetic resonance (NMR) spectroscopy confirmed the mass transfer of sugar molecules between the mixed sugar solution and kiwifruit chunks. The moisture distribution results highlighted that the infiltration of sugar molecules could induce a large amount of free water to escape from kiwifruit chunks and reduce the mobility of water molecules. The 12 h US-SUC-XOS group showed the lowest peak area of free water and the highest peak area of immobile water and bound water. In summary, different mixed sugar solutions mediate different degrees of mass transfer. In particular, SUC-XOS solution can retard the degradation of kiwifruit tissues, in turn contributing to the formation of good quality in kiwifruit chunks.